Copper(II) Triflate Catalyzed Regioselective and Enantioselective Propargylation of Isatin Derivatives by Using Allenylboronic Acid Pinacol Ester. Issue 11 (22nd March 2018) - Gupta, Naveen; Tak, Rajkumar; Nazish, Mohd; Jakhar, Ajay; Khan, Noor‐ul H.; Kureshy, Rukhsana I.
Abstract : We report a simple protocol for the synthesis of homopropargyl alcohols with isatin derivatives under milder conditions for the first time. The excellent regioselectivity and yields were observed with copper triflate as a Lewis‐acid catalyst and allenylboronic acid pinacol ester as a nucleophile in aqueous media. A gram‐scale synthesis was done to check the efficiency of the protocol with retention in selectivity. Further one‐step functionalization of these homopropargyl alcohols was established as the synthetic application of these alkynes. The enantioselective synthesis of these chiral propargyl alcohols has also been explored for the first time with an enantiomeric ratio up to 12:88. Abstract : Regioselective propargylation of isatins in aqueous media. With this protocol we could achieve propargyl alcohols in high yields with wide substrate scope. The enantioselective version was also explored to yield chiral alcohols with er up to 12:88, which is reported for the first time.